PERANCANGAN APLIKASI PENGELOLAAN INVENTARIS MENGGUNAKAN METODE WATERFALL BERBASIS WEB - Naufal, Naufal Rizqiananda (CV SWA Anugerah, 2025)
Efficient and accurate inventory management is an important aspect in supporting organizational operations. However, manual methods often cause inefficiencies, recording errors, and delays in generating reports. This research aims to design and implement a web-based inventory management application using the Waterfall method. This method was chosen because of its systematic and structured approach to software development. The designed application has main features such as recording incoming and outgoing goods, creating automatic reports, and managing inventory data in real-time. Test results show that this application is able to increase the efficiency of item recording time by up to 80% and reduce report creation time by more than 99%. In addition, the recording error rate can be completely eliminated during the testing period. This application has also proven to be stable in handling simultaneous access by up to 20 active users with key feature response times of under 2 seconds. User Acceptance Testing (UAT) testing resulted in an average user satisfaction score of 4.6 out of 5, which shows that this application is easy to use and relevant to user needs. This research concludes that a web-based inventory management application using the Waterfall method is effective in increasing the efficiency, accuracy and accessibility of inventory management. Development of additional features, such as stock notifications and integration with financial systems, is recommended to improve the application's functionality in the future.